The Impact of the Buyer Participation in CSR Activities on a Supply Chain - Ma Jin-Hee; ChoiSeokBeom; 안영효 (Journal of distribution science, 2018)
Purpose - This study aims to investigate whether the buyer's participation in CSR activities can affect the informal cooperation and relationship beyond formal cooperation and relationship. Research design, data, and methodology - We defined the research model and selected variables(monitoring and contracts by the buyer, formal cooperation & relationship, and informal cooperation & relationship). After completing the questionnaire, we analyzed 319 manufacturing companies. Prior to the hypothesis testing, Exploratory factor analysis(EFA) and confirmatory factor analysis(CFA) were conducted to check for discriminant validity and convergent validity. Results - The stronger the buyer monitoring on the company's CSR activities, the more positive it affects the formal business cooperation. On the other hand, strong buyer monitoring did not affect formal business relationships. Therefore, even if buyers' monitoring of CSR activities is strong, it does not mean that the formal business relationship is improved, but it means that it is possible to improve the formal business cooperation. Conclusions - This study shows that the stronger the buyer monitoring on the supplier's CSR activities, the more positive it affects formal cooperation. It also demonstrates that formal business cooperation between the supplier and the buyer, that is, sharing goals and works for CSR activities, has a positive effect on relationships based on emotional exchange and commitment. KCI Citation Count: 2